Regulatory and Procedural Barriers to Trade in Armenia - United Nations (United Nations, 2019)
This study highlights the challenges faced by international traders and the types of efforts needed for greater regional and global economic integration. It will support the government at formulating trade reforms, and therefore enable the government to ensure the successful achievement of the global sustainable development goals. The recommendations were born out of consultations with the government, drawing on extensive field surveys targeting supply chain actors, legislative analysis and trade indices. The study also featured a special focus on female-owned enterprises, with a view to gaining a better understanding of the specific challenges to increasing their participation in international trade.